C-type lectin (SpCTL) through its binding to Spβ-integrin regulates antimicrobial peptide synthesis in mud crab (Scylla paramamosain) during Vibrio parahaemolyticus infection - Wei Yang; Yuyong He; Huifen Liang; Junyuan Lin; Ngoc Tuan Tran; Zhinuo Du; Ming Zhang; Ruhan Chen; Yuqing Zheng; Xu Meng; Shengkang Li (Aquaculture Reports)
C-type lectin (CTL) is a widespread pattern recognition receptor that recognizes and binds to pathogen-associated molecular patterns on the surface of pathogens and mediates a series of immune responses in animals. In this study, the mud crab SpCTL cDNA was cloned and functionally characterized. Phylogenetic analysis showed that SpCTL was closely related to Eriocheir sinensis with 81 % homology. The SpCTL mRNA was expressed in hemocytes and hepatopancreas under infection with Vibrio parahaemolyticus (Vp), lipopolysaccharide (LPS), white spot syndrome virus (WSSV), or Poly I: C (PIC). Furthermore, the recombinant SpCTL (rSpCTL) protein was purified, and the antimicrobial activity of rSpCTL was analyzed. The results showed that the rSpCTL had an agglutination activity on Staphylococcus aureus, Streptococcus b, Escherichia coli, Vp, Aeromonas hydrophila, Vibrio alginolyticus, and Saccharomyces cerevisiae in the presence of calcium ions. rSpCTL showed strong adhesion to Streptococcus b, E. coli and V. alginolyticus. Also, rSpCTL revealed good bacteriostatic activity on S. aureus, Streptococcus b, E. coli, Vp, A. hydrophila, and V. alginolyticus, with a dose-dependent manner, but not on S. cerevisiae. Besides, the mass spectrometry results showed that the expression of Spβ-integrin and Spflotillin-2 (SpFLT-2) was significantly down-regulated at 6, 24, and 48 h when the expression of SpCTL was knocked down by RNAi, whereas the change of FLT-2 was not significant (first up-regulated and then down-regulated) at 6 and 24 h. Our results found that under stimulation of Vp, SpCTL recognizes the bacterium and binds to Spβ-integrin, which transmits signals into hemocyte and subsequently regulates the expression of antimicrobial peptides (SpALF1, SpALF3–5) and protects mud crabs from infection. Collectively, the results indicate that SpCTL has agglutination, bacteriostatic, and adhesion activities. SpCTL play an important role in the innate immunity of mud crabs.